Okra (Abelmoschus esculentus L. Moench) prevents obesity by reducing lipid accumulation and increasing white adipose browning in high-fat diet-fed mice. Issue 22 (31st October 2022) - Jin, Heegu; Oh, Hyun-Ji; Cho, Sehaeng; Lee, Ok-Hwan; Lee, Boo-Yong
Abstract : Anti-obesity effects of OKC in HFD-fed obese mice. Treatment with OKC reduced lipid accumulation and promoted energy expenditure through browning. This was associated with improvements in the hyperglycemia, dyslipidemia, and hepatic steatosis. Abstract : Obesity is characterized by excessive fat accumulation owing to an imbalance between energy intake and expenditure. The suppression of lipid accumulation and the promotion of white adipose tissue (WAT) browning, which increases energy expenditure, may protect against obesity. Here, we demonstrate that okra complex (OKC) significantly reduces the body and WAT mass of mice by inhibiting adipogenesis and lipogenesis. We also show that OKC administration reduces fasting blood glucose and serum cholesterol and triglyceride (TG) concentrations and ameliorates liver steatosis in HFD-fed obese mice. In addition, OKC activates the protein kinase A (PKA) signaling pathway, which increases lipolysis; and induces the uncoupling protein 1 (UCP1)-mediated "browning" of WAT. These findings demonstrate that OKC has potentially beneficial effects on lipid metabolism and upregulates thermogenesis, which implies that it may be useful for the therapy and/or prevention of obesity and related metabolic diseases.